Fabric

By attaching ammonium salt polymer compounds to cellulose fiber fabrics, the problems of poor fast drying properties and insufficient washing durability of cellulose fiber fabrics are solved, and efficient water absorption and quick drying properties and durability are achieved, and the process is simple and cost-effective.

CN120193414APending Publication Date: 2025-06-24TORAY FIBER RES INST(CHINA) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311768928.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-21
Publication Date
2025-06-24

AI Technical Summary

Technical Problem

The existing cellulose fiber fabrics have poor fast drying properties, and the molecular weight of modified silicones is large, so they cannot enter the fiber, resulting in insufficient washing durability.

Method used

Using 50% by weight of cellulose fibers, an ammonium salt polymer compound with hydrophilic and hydrophobic groups is attached to the surface, and combined with the negative charge on the cellulose fibers through ionic action, the rapid water absorption and washing durability are improved.

Benefits of technology

It significantly improves the water absorption and quick-drying properties of the fabric and wash durability. At the same time, the process is simple and the cost is low, and it has no effect on the feel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004621983560000021
    Figure BDA0004621983560000021
  • Figure BDA0004621983560000022
    Figure BDA0004621983560000022
  • Figure BDA0004621983560000071
    Figure BDA0004621983560000071
Patent Text Reader

Abstract

The invention discloses a fabric. The fabric contains more than 50 wt% of cellulose fibers, an ammonium salt high-molecular compound is attached to the surfaces of the cellulose fibers, R1 and R2 grafted on the ammonium salt high-molecular compound are respectively alkyl, and R3 and R4 are respectively one or more of carboxylic acid group, sulfonic acid group, phosphate group, amino, ether group, hydroxyl and aldehyde group. The processing method of the fabric is simple and easy to implement, and the fabric has excellent water-absorbing and quick-drying performance and high washing durability and can be used for producing underwear, sportswear, shirts and other products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of textiles, and particularly relates to a water-absorbing and quick-drying fabric. Background Art

[0002] With the improvement of people's living standards and the development of the textile industry, consumers' pursuit of the comfort and functionality of clothing is also getting higher and higher. Among them, water absorption and quick drying are particularly concerned. Cellulose fiber fabrics are deeply loved by consumers for their good hygroscopicity, skin-friendly properties, etc. However, since the hydrophilic groups in cellulose molecules are combined with water molecules by hydrogen bonds, it is difficult for the absorbed water to evaporate, so the quick-drying property of such fabrics is poor.

[0003] In order to improve the water absorption and quick-drying properties of cellulose fiber fabrics, many studies have been carried out. For example, Chinese Patent Document CN105463859A discloses a water-absorbing and quick-drying fabric, and specifically discloses that at least 30% or more of the fibers in the fabric are cellulose fibers. Part of the hydroxyl groups in these cellulose fibers are blocked by polyether-modified amino silicone, and the content of unblocked active hydroxyl groups is 0.7 - 4.2 mmol / g, effectively improving the water absorption and quick-drying properties of fabrics with a high cellulose fiber content. However, due to the relatively large molecular weight of the modified silicone used, it cannot enter the fiber interior. Even if it reacts with the fiber, it can only be adsorbed on the fiber surface in a directional manner, and the washing durability still needs to be further improved.

[0004] Again, Chinese Patent Document CN109183407A discloses a preparation method of a moisture-absorbing and quick-drying fabric, and specifically discloses that the fabric is impregnated and rolled in a moisture-absorbing and quick-drying liquid, and the moisture-absorbing and quick-drying liquid includes a moisture-absorbing and quick-drying agent and water. The moisture-absorbing and quick-drying agent includes octamethylcyclotetrasiloxane, 2,3-epoxypropyltrimethyl, rosin, sodium styrenesulfonate, and dodecafluoroheptyl methacrylate, obtaining a good moisture-absorbing and quick-drying effect. However, due to the use of rosin as an adhesive, it will not only affect the hand feeling of the fabric, but also the process is complex and the cost is high. Summary of the Invention

[0005] The purpose of the present invention is to provide a water-absorbing and quick-drying fabric with simple process, low cost, high washing durability and no influence on the hand feeling.

[0006] The technical solution of the present invention is:

[0007] The fabric of the present invention contains 50% by weight or more of cellulose fibers. Among them, an ammonium salt polymer compound with the following structure is attached to the surface of the cellulose fibers.

[0008]

[0009] Among them, R1 and R2 are hydrocarbon groups respectively; R3 and R4 are each one or more of a carboxyl group, a sulfonic acid group, a phosphoric acid group, an amino group, an ether group, a hydroxyl group, and an aldehyde group.

[0010] In the present invention, the ammonium salt polymer compound attached to the cellulose fiber has both a hydrophilic group and a hydrophobic group, and the arrangement of the hydrophilic group and the hydrophobic group on the cellulose fiber changes with the change of the dry and wet states of the fabric; moreover, the positive charge carried by the ammonium salt polymer compound combines with the negative charge on the surface of the cellulose fiber, which not only improves the water absorption and quick-drying property of the fabric, but also greatly improves the washing durability of the fabric. The processing cost is low, and it can be used for producing underwear, sportswear, shirts, etc. Detailed implementation mode

[0011] The fabric of the present invention contains more than 50% by weight of cellulose fiber, and the surface of the cellulose fiber is attached with an ammonium salt polymer compound having the following structure,

[0012]

[0013] Among them, R1 and R2 are hydrocarbon groups respectively; R3 and R4 are each one or more of a carboxyl group, a sulfonic acid group, a phosphoric acid group, an amino group, an ether group, a hydroxyl group, and an aldehyde group.

[0014] In the present invention, the type of cellulose fiber is not particularly limited, and it can be natural cellulose fibers such as cotton fiber and hemp fiber, or regenerated cellulose fibers such as viscose, cuprammonium, and acetate. If the content of cellulose fiber in the fabric is less than 50% by weight, then under the same conditions, the attachment amount of the ammonium salt polymer compound will decrease, and the washing durability of the fabric is relatively poor.

[0015] The above-mentioned ammonium salt polymer compound has a hydrophilic group and a hydrophobic group, and the arrangement of the hydrophilic group and the hydrophobic group on the cellulose fiber changes with the change of the dry and wet states of the fabric. In the dry state, the groups arranged on the side facing the air are R1 and R2 as hydrophobic groups, while in the wet state, the hydrophilic group has a higher affinity for water. Under the action of the affinity, the positions of the groups are reversed, and the groups arranged on the side facing the air become R3 and R4 as hydrophilic groups. That is to say, there are more hydrophilic groups on the surface. These hydrophilic groups combine with water molecules, accelerating the diffusion rate of water, increasing the diffusion area of water on the fabric surface, increasing the water evaporation amount per hour, and improving the quick-drying property. And, the above-mentioned ammonium salt polymer compound carries a positive charge and combines with the negative charge on the cellulose fiber through ionic action, effectively improving the washing durability. Preferably, R1 and R2 are alkyl groups respectively, and R3 and R4 are each one or more of a carboxyl group, a sulfonic acid group, a phosphoric acid group, an amino group, an ether group, a hydroxyl group, and an aldehyde group with a carbon atom number less than 18.

[0016] Among them, the adhesion amount of the ammonium salt polymer compound can be adjusted as needed, preferably 0.8-1.5% by weight. In the present invention, if the adhesion amount of the ammonium salt polymer compound is less than 0.8% by weight, the water absorption of the fiber surface has a downward trend and may affect the diffusion area, so it is not preferred; if the adhesion amount is higher than 1.5% by weight, the surface water absorption reaches saturation and the cost has an increasing trend, so it is not preferred.

[0017] Preferably, the surface of the cellulose fiber of the present invention is also attached with a polycationic compound. The polycationic compound refers to a compound with a cationic group and has good water solubility. They can undergo covalent cross-linking through an affinity with the cellulose fiber to produce a strong adsorption effect, while obtaining excellent color fixation effects without affecting the water absorption and quick-drying properties of the fabric. When using anionic dyes, the polycationic compound can also combine with these anionic dyes by ionic bonds to further improve the color fastness of the fabric. In the present invention, the polycationic compound is preferably one or more of a primary amine salt compound, a secondary amine salt compound, a tertiary amine salt compound, and a quaternary ammonium salt compound. Among them, the quaternary ammonium salt compound has the strongest cationicity, so it is more preferred.

[0018] The fabric of the present invention can be composed of 100% cellulose fiber or can be composed of cellulose fiber and synthetic fiber. Among them, the type of synthetic fiber is not particularly limited and can be ordinary polyester fiber (ordinary PET), modified polyester fiber (modified PET), polyamide fiber, polyacrylonitrile fiber, polyurethane fiber (PU), polyvinyl acetal fiber, etc.

[0019] Preferably, the initial water absorption of the fabric measured by the dropping method according to JIS L 1097:2010 is within 1 second, and after washing 10 times by the C4G method in the JIS L 1930:2014 standard and then measuring the water absorption of the fabric by the dropping method according to JIS L 1097:2010, it is within 1 second.

[0020] Preferably, the initial residual moisture rate of the fabric is within 30% after 60 minutes under the conditions of a temperature of 20°C ± 2°C and a relative humidity of 65% RH ± 5% RH, and the residual moisture rate of the fabric is still within 30% after washing 10 times by the C4G method in the JIS L 1930:2014 standard. Under the same conditions, the less the residual moisture rate of the fabric after 60 minutes, the faster the drying speed of the fabric, the shorter the drying time, and the better the quick-drying property.

[0021] The water-absorbing and quick-drying fabric of the present invention has no particular limitation on its manufacturing method and can be obtained by the following method: treating a woven or knitted grey fabric with a cellulose fiber content of 50% by weight or more with a finishing solution containing the above-mentioned ammonium salt polymer compound to obtain a product. The ammonium salt polymer compound can be a commercially available product or a self-synthesized product, and its dosage is adjusted according to needs, preferably 1.2 to 2.0% by weight.

[0022] The above treatment method has no particular limitation and can be bath treatment or padding. The specific conditions for bath processing are as follows: treating at a temperature of 40°C for 30 to 60 minutes, and then drying at a temperature of 110 to 130°C. The specific conditions for padding are as follows: after one-dip one-roll or two-dip two-roll, followed by heat treatment at a temperature of 110 to 130°C for 2 to 5 minutes. Padding is preferred, and one-dip one-roll processing is more preferred.

[0023] Within the scope not affecting the purpose of the present invention, dyes and various dyeing auxiliaries can also be used in the finishing solution according to the need for coloring. A fixing agent of polycationic compound is preferably used, and its dosage is adjusted according to needs, preferably 0.2 to 0.5% by weight.

[0024] The present invention will be further described below in conjunction with examples and comparative examples. The physical property parameters of the present invention are measured according to the following methods:

[0025] (1) Content of cellulose fiber

[0026] Randomly cut 10 fabric specimens with a mass of about 1 g each. Take 1 of them and place it in a constant temperature blast drying oven, dry it at 105°C for 4 hours until it reaches a constant mass. Then take out the specimen from the oven, put it in a desiccator and cool it for 1 hour. After cooling, place the desiccator on a balance and weigh it within 2 minutes, record it as m1. Measure 1000 mL of concentrated sulfuric acid (density ρ = 1.84 g / mL, AR, mass fraction 98%, Sinopharm Group Co., Ltd.) with a measuring cylinder, slowly add it to 1100 mL of tertiary water, and control its density at 1.495 - 1.498 g / mL at 20°C. Put the specimen and 100 mL of the prepared sulfuric acid solution into a conical flask, shake it vigorously at 15 - 25°C for 1 minute, let it stand for 15 minutes, then shake - stand again, repeat this step 3 times. Then rinse it with running water for 10 minutes, soak it in dilute ammonia water for 1 minute, then rinse it with running water again, and finally drain the liquid by vacuum suction. Dry it at 105°C for 4 - 6 hours, put it in a desiccator and let it stand and cool for 30 minutes, and weigh the mass m2. Calculate the content of cellulose fiber according to the following formula: Content of cellulose fiber (%) = [(m1 - m2)

[0027] / m1】 * 100%. Measure the remaining 9 portions in the same way, and take the average value as the content of the cellulose fiber of the present invention.

[0028] (2) Ammonium salt polymer compound and content

[0029] Cut the fabric to be tested into powder, take a small amount and mix it with dried potassium bromide, then press it into a film, and use an infrared spectrometer to measure the infrared spectrum. According to different chemical bonds or functional groups, different absorption peaks will appear in the infrared spectrum due to different absorption frequencies, so as to determine the types of various groups in the ammonium salt polymer compound. In the infrared spectrum, if a sharp strong absorption peak appears near 1030 cm -1 it indicates that the fabric is attached with an ammonium salt polymer compound.

[0030] If there are absorption peaks at 2975 - 2845 cm -1 , 1460 cm -1 and 1380 cm -1 it indicates that the R group of the ammonium salt polymer compound contains a monovalent saturated hydrocarbon group in the hydrocarbon group; if there are absorption peaks at 1620 - 1670 cm -1 , 730 - 990 cm -1 and 3075 - 3090 cm -1 or if there are absorption peaks at 2100 - 2140 cm -1 , 2190 - 2260 cm -1 , 610 - 680 cm -1 and 3310 - 3300 cm -1 it indicates that the R group of the ammonium salt polymer compound is a monovalent unsaturated hydrocarbon group in the hydrocarbon group; if there are absorption peaks at 1450 - 1650 cm -1 , 650 - 900 cm -1 and 3000 - 3100 cm -1 it indicates that the R group of the ammonium salt polymer compound is an aromatic group in the hydrocarbon group; if there are absorption peaks at 1680 - 1725 cm -1 and 2500 - 3300 cm -1 it indicates that the R group of the ammonium salt polymer compound contains a carboxyl group; if there are absorption peaks at 1300 - 1000 cm -1 and 1400 - 1250 cm -1 it indicates that the R group of the ammonium salt polymer compound contains a sulfonic acid group; if there are absorption peaks at 1200 - 1000 cm -1 and 3000 - 3600 cm -1 it indicates that the R group of the ammonium salt polymer compound contains a phosphate group; if there is a broad absorption peak at 3100 - 3500 cm -1 and 1600 - 1650 cm-1 If there is an absorption peak at this position, it indicates that the R group of the ammonium salt polymer compound contains an amino group; at 1060 - 1150 cm -1 If there is an absorption peak at this position, it indicates that the R group of the ammonium salt polymer compound contains an ether group; at 3200 - 3670 cm -1 and 1410 - 1100 cm -1 If there are strong absorption peaks at this position, it indicates that the R group of the ammonium salt polymer compound contains a hydroxyl group; at 1680 - 1750 cm -1 and 2700 - 2900 cm -1 If there is an absorption peak at this position, it indicates that the R group of the ammonium salt polymer compound contains an aldehyde group.

[0031] Cut the fabric into pieces as samples and put them into a glass cup. Add trifluoroacetic acid and chloroform. After the samples are fully dissolved, drop them into a methanol solution to precipitate the solid. Dissolve and precipitate the samples 3 - 5 times to obtain purified solid samples; put the obtained solid samples into a vacuum drying oven and dry them at 80 °C for 24 hours. Weigh 20 mg of the purified and dried samples and put them into a nuclear magnetic tube, and add deuterated reagent D2O; Test the samples dissolved in D2O using a Mercury - VX - 300 nuclear magnetic resonance spectrometer (Varian, USA). According to the nuclear magnetic resonance spectrum ( 1 1H NMR, with TMS as the reference standard) spectrum and chemical shift, the connection positions of each group can be judged.

[0032] Quantitative analysis of the ammonium salt polymer compound is carried out according to the contents of R3 and R4. Among them, the contents of the ammonium salt polymer compounds with R3 and R4 groups containing carboxyl groups are determined by acid - base titration; the contents of the ammonium salt polymer compounds with R3 and R4 groups containing sulfonic acid groups are determined by elemental quantitative analysis of sulfur elements; the contents of the ammonium salt polymer compounds with R3 and R4 groups containing phosphate groups are determined by elemental quantitative analysis of phosphorus elements; the contents of the ammonium salt polymer compounds with R3 and R4 groups containing amino groups are determined by measuring the content of terminal amino acids through mass spectrometry analysis; the contents of the ammonium salt polymer compounds with R3 and R4 groups containing ether groups or hydroxyl groups are determined after analyzing the contents of ether groups and hydroxyl groups through the nuclear magnetic resonance spectrum (1H NMR, with TMS as the reference standard) spectrum and chemical shift; the ammonium salt polymer compounds with R3 and R4 groups containing aldehyde groups are determined after quantitatively analyzing the content of terminal aldehyde groups through infrared spectroscopy.

[0033] (3) Polycationic compound

[0034] The polycationic compound is determined by measuring the cationic degree. The cationic degree is a measure of the solubility and activity of cations in a solution. The higher the cationic degree, the greater the solubility of cations in the solution, the higher the activity, the stronger the cationicity, and the stronger the ability to undergo chemical reactions. The cationic degree is determined by colloid titration. Weigh 5 g (accurate to 0.0001 g) of the polycationic compound after drying to constant weight with a weighing paper and put it into a 250 mL weighing bottle. Add 100 mL of distilled water, stir until dissolved, then add the pre-prepared HCl dropwise to the sample solution (prepared by adding 9 mL of concentrated hydrochloric acid to 1000 mL of water in advance), adjust the pH to 3 - 4, add 2 drops of T.B. indicator, and titrate with the PAMPSNa standard solution. When the color of the solution changes from blue to purplish red, it is the titration end point. At least three parallel experiments are carried out, and the average value is taken as the consumed volume of PAMPSNa and recorded as V1; at the same time, a blank experiment is carried out, and the consumed volume of PAMPSNa for titration is recorded as V0;

[0035] The cationic degree Am = MC(V1 - V0)1000m * 100%

[0036] In the formula: M is the relative molecular mass of the cationic chain link

[0037] C is the molar concentration of PAMPSNa, with the unit mol / L

[0038] V1 is the volume of PAMPSNa consumed during titration, with the unit mL

[0039] V0 is the volume of PAMPSNa consumed during blank determination, with the unit mL

[0040] m is the mass of the sample, with the unit g.

[0041] (4) Determination of primary amine salt compounds, secondary amine salt compounds, tertiary amine salt compounds and quaternary ammonium salt compounds

[0042] Cut the fabric to be tested into powder, take a small amount and mix it with dried potassium bromide, then press it into a film, and use an infrared spectrometer to measure the infrared spectrum. If there are two medium-intensity absorption peaks at 3500 - 3300 cm -1 and the peak shape is relatively wide and the intensity is medium at 900 - 650 cm -1 then it contains primary amine salt compounds; if there is only one absorption peak in the 3500 - 3300 cm -1 region, then it contains secondary amine salt compounds; if there is no absorption peak in the 3500 - 3300 cm -1 region, then it contains tertiary amine salt compounds; if there is a sharp strong absorption peak near 1030 cm -1 then it contains quaternary ammonium salt compounds.

[0043] (5) Water absorbency

[0044] Determined by the dropping method according to JIS L 1097:2010.

[0045] (6) Residual moisture content

[0046] Cut 5 pieces of the fabric to be tested with a size of 10 cm * 10 cm. Take one of them, first place it in an oven at 50 °C for 1 hour, then take it out and condition it in an environment with a temperature of 20 °C ± 2 °C and a relative humidity of 65% RH ± 5% RH for 24 hours and then weigh it, record as M0. Drop 0.3 mL of water on the side to be used close to the skin side and then weigh it, record as M1. Hang it vertically on a fiber product drying speed tester (manufactured by Nissin Kagaku Co., Ltd., model DST-5200B), measure the weight of the fabric every 5 minutes, and record the mass after 60 minutes as M2. Calculate the residual moisture content according to the following formula: Residual moisture content (%) = [(M2 - M0) / (M1 - M0)] * 100%. Repeat the above test steps for the remaining 4 test samples, and take the average value as the residual moisture content of the fabric of the present invention.

[0047] (7) Washing method

[0048] Wash 10 times according to the C4G method in JIS L 1930:2014 standard.

[0049] The chemicals used in the following examples and comparative examples are as follows:

[0050] (1) Ammonium salt polymer A (manufactured by Hubei Ruike Chemical Co., Ltd.):

[0051] Coconut oil-based dihydroxyethyl polyether methyl ammonium chloride

[0052]

[0053] (2) Ammonium salt polymer B (manufactured by Jiaxing Aisen Chemical Co., Ltd.):

[0054] Bis(2-hydroxyethyl)dimethyl ammonium chloride

[0055]

[0056] (3) Ammonium salt polymer C (manufactured by American Custom Chemicals Corporation):

[0057] N-(carboxymethyl)-2-hydroxy-N,N-dimethyl-, inner salt

[0058]

[0059] (4) Ammonium salt polymer compound D (manufactured by Henan Tianfu Chemical Co., Ltd.):

[0060] 1-Propanaminium,3-butoxy-2-hydroxy-N-(2-hydroxy-3-sulfopropyl)-

[0061] N,N-dimethyl-, inner salt

[0062]

[0063] (5) Ammonium salt polymer compound E (manufactured by Shenzhen Aituo Chemical Co., Ltd.):

[0064] (Carboxymethyl) dodecyldimethylammonium chloride

[0065]

[0066] (6) Ammonium salt polymer compound F (manufactured by Wuhan Karnox Technology Co., Ltd.):

[0067] Methyl trialkylammonium chloride

[0068]

[0069] (7) Fixative A (manufactured by Kunshan Sheng'an Biotechnology Co., Ltd.): Polydimethyldiallylammonium chloride.

[0070] (8) Fixative B: (Self-made, cationic degree is 6.5 mmol / g)

[0071] Weigh 16.05 g of ammonium chloride and put it into a four-necked flask. Add 30.93 g of ethylenediamine. Heat up to 90 °C and stir for 1 hour. Then add 25.20 g of dicyandiamide and 20.00 g of ethylene glycol. Heat up to 130 °C. Stop heating when no gas is released. Wait until the temperature drops to 90 °C. Add 70.00 g of distilled water. Adjust the pH to 6 - 7 with acetic acid solution to obtain Fixative B.

[0072]

[0073] (9) Fixative C (manufactured by Nagase Fine Chemicals Co., Ltd.):

[0074] Polymer of sodium hydroxybenzenesulfonate, formaldehyde and 4,4'-dihydroxybenzophenone

[0075]

[0076] Example 01:

[0077] Select a knitted fabric made of 40 English cotton yarn and 50D / 72f PET DTY. Among them, the cotton fiber content is 70% by weight. Use reactive dye Black M 4.0o.w.f. (manufactured by Huntsman International LLC), Na2SO4 60g / L (manufactured by Sinopharm Group Co., Ltd.), and Na2CO3 20g / L (manufactured by Sinopharm Group Co., Ltd.) to dye at 60°C for 60 minutes, wash with clear water 3 times, then soak in 1g / L glacial acetic acid (manufactured by Sinopharm Group Co., Ltd.) at 50°C for 20 minutes, wash with clear water 3 times, then soak in 3g / L soap detergent ESKUDOR (manufactured by Nihon Kayaku (China) Co., Ltd.) at 70°C for 20 minutes, wash with clear water 3 times, and dry to obtain a colored fabric. Put the colored fabric into a treatment solution composed of ammonium salt polymer A (coconut oil-based dihydroxyethyl polyether methyl ammonium chloride, 20g / L, manufactured by Hubei Ruike Chemical Co., Ltd.) and water for one-dip-one-roll treatment (the liquor pickup rate is 70%), and then dry it using a hot air type needle plate stenter at 130°C for 2 minutes to obtain the water-absorbing and quick-drying fabric of the present invention. The test results of various properties are shown in Table 1.

[0078] Example 02:

[0079] Select a knitted fabric with a cotton fiber content of 90% by weight for processing, and the rest is the same as Example 01 to obtain the water-absorbing and quick-drying fabric of the present invention. The test results of various properties are shown in Table 1.

[0080] Example 03:

[0081] Select a knitted fabric with a cotton fiber content of 50% by weight for processing, and the rest is the same as Example 01 to obtain the water-absorbing and quick-drying fabric of the present invention. The test results of various properties are shown in Table 1.

[0082] Example 04:

[0083] Adjust the dosage of ammonium salt polymer A to 8g / L, and the rest is the same as Example 01 to obtain the water-absorbing and quick-drying fabric of the present invention. The test results of various properties are shown in Table 1.

[0084] Example 05:

[0085] Adjust the dosage of ammonium salt polymer A to 15g / L, and the rest is the same as Example 01 to obtain the water-absorbing and quick-drying fabric of the present invention. The test results of various properties are shown in Table 1.

[0086] Example 06:

[0087] The treatment liquid consists of an ammonium salt polymer compound B (bis(2-hydroxyethyl)dimethylammonium chloride, 20 g / L, manufactured by Jiaxing Aisen Chemical Co., Ltd.) and water. The rest is the same as in Example 01, obtaining the water-absorbing and quick-drying fabric of the present invention. The test results of various properties are shown in Table 1.

[0088] Example 07:

[0089] The treatment liquid consists of an ammonium salt polymer compound C (N-(carboxymethyl)-2-hydroxy-N,N-dimethyl-, inner salt, 20 g / L, manufactured by American Custom Chemicals Corporation) and water. The rest is the same as in Example 01, obtaining the water-absorbing and quick-drying fabric of the present invention. The test results of various properties are shown in Table 1.

[0090] Example 08:

[0091] The treatment liquid consists of an ammonium salt polymer compound D (1-Propanaminium, 3-butoxy-2-hydroxy-N-(2-hydroxy-3-sulfopropyl)-N,N-dimethyl-, inner salt; 20 g / L, manufactured by Henan Tianfu Chemical Co., Ltd.) and water. The rest is the same as in Example 01, obtaining the water-absorbing and quick-drying fabric of the present invention. The test results of various properties are shown in Table 1.

[0092] Example 09:

[0093] The treatment liquid consists of an ammonium salt polymer compound A (cocoalkyldihydroxyethyl polyether methyl ammonium chloride, 20 g / L, manufactured by Hubei Ruike Chemical Co., Ltd.), a color fixing agent A (polydimethyldiallylammonium chloride, 10 g / L, Kunshan Sheng'an Biotechnology Co., Ltd.) and water. The rest is the same as in Example 01, obtaining the water-absorbing and quick-drying fabric of the present invention. The test results of various properties are shown in Table 1.

[0094] Example 10:

[0095] The treatment liquid consists of an ammonium salt polymer compound A (cocoalkyldihydroxyethyl polyether methyl ammonium chloride, 20 g / L, manufactured by Hubei Ruike Chemical Co., Ltd.), a color fixing agent B (secondary amine salt compound, 10 g / L, self-made) and water. The rest is the same as in Example 01, obtaining the water-absorbing and quick-drying fabric of the present invention. The test results of various properties are shown in Table 2.

[0096] Example 11:

[0097] Select a knitted fabric formed by 75D / 48f viscose FDY and 50D / 72f PET DTY. Among them, the content of viscose fiber is 70% by weight, and the rest is the same as in Example 01, to obtain the water-absorbing and quick-drying fabric of the present invention. The test results of various properties are shown in Table 2.

[0098] Example 12:

[0099] The treatment liquid consists of ammonium salt polymer compound A (coconut oil-based dihydroxyethyl polyether methyl ammonium chloride, 20 g / L, manufactured by Hubei Ruike Chemical Co., Ltd.), fixing agent C (polymer of hydroxybenzenesulfonate, formaldehyde and 4,4'-dihydroxybenzenesulfone, 10 g / L, manufactured by Nagase Fine Chemical Co., Ltd.), and water. The rest is the same as in Example 01, to obtain the fabric of the present invention. The test results of various properties are shown in Table 2.

[0100] Comparative Example 01:

[0101] The content of cotton fiber in the knitted fabric is 40% by weight, and the rest is the same as in Example 01, to obtain the fabric. The test results of various properties are shown in Table 2.

[0102] Comparative Example 02:

[0103] The treatment liquid consists of ammonium salt polymer compound E ((carboxymethyl) dodecyl dimethyl ammonium chloride, 20 g / L, manufactured by Shenzhen Aituo Chemical Co., Ltd.) and water. The rest is the same as in Example 01, to obtain the fabric. The test results of various properties are shown in Table 2.

[0104] Comparative Example 03:

[0105] The treatment liquid consists of ammonium salt polymer compound F (methyl trialkyl ammonium chloride, 20 g / L, manufactured by Wuhan Karnos Technology Co., Ltd.) and water. The rest is the same as in Example 01, to obtain the fabric. The test results of various properties are shown in Table 2.

[0106] Table 1

[0107]

[0108] Table 2

[0109]

[0110] According to Table 1 and Table 2,

[0111] (1) From Example 05 and Example 04, it can be seen that under the same conditions, the fabric with an ammonium salt polymer compound adhesion amount of 1.2% by weight and the fabric with an ammonium salt polymer compound adhesion amount of 0.5% by weight, that is, the former has better quick-drying property and water-absorbing property before and after washing than the latter.

[0112] (2) As can be seen from Example 01 and Example 06, under the same conditions, compared with the fabric processed with ammonium salt polymer compound B, the water absorbency of the fabric processed with ammonium salt polymer compound A before and after washing is equivalent, and the residual moisture rate of the former before and after washing is slightly lower than that of the latter, that is, the quick-drying property of the former before and after washing is slightly better than that of the latter.

[0113] (3) As can be seen from Example 09 and Example 01, under the same conditions, compared with the fabric processed solely with ammonium salt polymer compound A, the water absorption and quick-drying property of the fabric processed with ammonium salt polymer compound A and fixing agent A together before and after washing is equivalent, that is to say, even with the use of a fixing agent, the water absorption and quick-drying property is not affected.

[0114] (4) As can be seen from Example 10 and Example 12, under the same conditions, compared with the fabric processed with a secondary ammonium salt compound fixing agent, the water absorption and quick-drying property of the fabric processed with a sulfonate compound fixing agent before and after washing are both superior.

[0115] (5) As can be seen from Comparative Example 01 and Example 03, under the same conditions, compared with the fabric with a cotton fiber content of 50% by weight, the water absorbency of the fabric with a cotton fiber content of 40% by weight before washing is equivalent, but the water absorbency of the former after washing is much worse than that of the latter.

[0116] (6) As can be seen from Comparative Example 02 and Example 01, under the same conditions, compared with the fabric processed with ammonium salt polymer compound A, the water absorption and quick-drying property of the knitted fabric processed with ammonium salt polymer compound E before and after washing are very poor. (7) As can be seen from Comparative Example 03 and Example 01, under the same conditions, compared with the fabric processed with ammonium salt polymer compound A, the water absorption and quick-drying property of the knitted fabric processed with ammonium salt polymer compound F before and after washing are very poor.

Claims

1. A fabric containing more than 50% by weight of cellulose fibers, characterized in that: The surface of the cellulose fiber is attached with an ammonium salt polymer compound having the following structure, wherein R1 and R2 are each a hydrocarbon group; R3 and R4 are each one or more of a carboxyl group, a sulfonic acid group, a phosphoric acid group, an amino group, an ether group, a hydroxyl group and an aldehyde group.

2. The fabric according to claim 1, characterized in that: The surface of the cellulose fiber is further attached with a polycationic compound.

3. The fabric according to claim 2, characterized in that: The polycationic compound is one or more of a primary amine salt compound, a secondary amine salt compound, a tertiary amine salt compound and a quaternary ammonium salt compound.

4. The fabric according to any one of claims 1 to 3, characterized in that: The water absorbency of the fabric at the initial stage is within 1 second as measured by the dropping method according to JIS L 1097:2010; the water absorbency of the fabric is within 1 second as measured by the dropping method according to JIS L 1097:2010 after washing 10 times by the C4G method in the standard of JIS L 1930:2014.

5. The fabric according to any one of claims 1 to 3, characterized in that: The initial residual moisture rate of the fabric is within 30%, and the residual moisture rate of the fabric is within 30% as measured after washing 10 times by the C4G method in the standard of JIS L 1930:2014.

Citation Information

Patent Citations

  • Water-absorption and rapid-drying fabric

    CN105463859A

  • Preparation method for hydroscopic and fast dry fabric

    CN109183407A